Persepsi Konsumen dalam Menentukan Keputusan Pembelian Produk Minuman dengan Klaim Kurang Gula - Fransisca Fransisca; Nurheni Sri Palupi; Didah Nur Faridah (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2016)
Limiting consumption of drinks containing high sugar can prevent diabetes especially type 2. Diabetes is one of non-communicable diseases that the number of sufferers is increasing every year. This opportunity is utilized by food industry to produce less sugar beverages. This study was aimed to analyze influence of demographic and respondent’s sugar consumption level on consumer’s perceptions, its influence on purchasing decisions and to analyze less sugar beverage product market opportunities compared with similar beverages without that claim among consumers and next generation. A survey was conducted on 150 respondents living in Jabodetabek, 20-54 years old, not a diabetic, and reading the food labels. There were 77.3% of total respondents had correct perception of less sugar correlated with sex, education, respondent's reducing sugar consumption effort and purchasing decision. People who were trying to reduce sugar had 3 times more likely to have correct perception than people who did not. People had more correct perception of less sugar (according to regulation), they increasingly choce less sugar products. The result of this survey showed that encouraging children to consume less sugar drinks was more prioritized manner to limit children’s sugar level consumption rather than replaced with sweetener.